Associations of dietary carbohydrates, glycaemic index and glycaemic load with risk of bladder cancer: a case–control study. Issue 9 (9th October 2017) - Augustin, Livia S. A.; Taborelli, Martina; Montella, Maurizio; Libra, Massimo; La Vecchia, Carlo; Tavani, Alessandra; Crispo, Anna; Grimaldi, Maria; Facchini, Gaetano; Jenkins, David J. A.; Botti, Gerardo; Serraino, Diego; et al.
Abstract: Carbohydrate foods with high glycaemic index (GI) and load (GL) may negatively influence cancer risk. We studied the association of dietary carbohydrates, GI, GL, intake of bread and pasta with risk of bladder cancer using data from an Italian case–control study. The study included 578 men and women with histologically confirmed bladder cancer and 608 controls admitted to the same hospitals as cases for acute, non-neoplastic conditions. OR were estimated by logistic regression models after allowance for relevant confounding factors. OR of bladder cancer for the highest v . the lowest quantile of intake were 1·52 (95 % CI 0·85, 2·69) for available carbohydrates, 1·18 (95 % CI 0·83, 1·67) for GI, 1·96 (95 % CI 1·16, 3·31, P trend <0·01) for GL, 1·58 (95 % CI 1·09, 2·29, P trend =0·03) for pasta and 1·92 (95 % CI 1·28, 2·86, P trend <0·01) for bread. OR for regular consumption of legumes and whole-grain products were 0·78 (95 % CI 0·60, 1·00) and 0·82 (95 % CI 0·63, 1·08), respectively. No heterogeneity in risks emerged across strata of sex. This case–control study showed that bladder cancer risk was directly associated with high dietary GL and with consumption of high quantity of refined carbohydrate foods, particularly bread. These associations were apparently stronger in subjects with low vegetable consumption.